(untitled) (International Journal of Engineering and Computer Science, 2018)
Digital images are used for a variety of applications such as news media, film industry, military application etc. With the help of image editing software tools, it is easy to alter the content of an image. So the content of an image is no longer believable nowadays. Contrast enhancement is an important factor for image enhancement. There are various types of techniques to create forged images for various intentions. When an attacker manipulates an image, contrast enhancement is used for avoiding traces left by the image forgery. There are so many methods to enhance contrast of an image. So in order to detect an image forgery, it is necessary to perform contrast enhancement detection. This paper reviews various methods for detecting contrast enhancement in digital images.